Приведите уравнение (x-5)(2x+3)-(x+4)(4-x)=2x+5 к виду ax2+bx+c=0

A.3x2+5x-26=0

B.X2-9x-12=0

C.6x2-5x+12=0

D.X2-3x-12=0

2

Ответы и объяснения

2013-01-08T13:28:22+04:00
2013-01-08T13:28:43+04:00

(2x^2+3x-10x-15)-(4x-x^2+16-4x)=2x+5

2x^2+3x-10x-15-4x+x^2-16+4x=2x+5

3x^2...............................................................

Дальше решать не имеет смысла, подходит только вариант Д...................................................................................................................!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

Ответ: Д